Propuesta de mejoramiento para el control de inundaciones del sector Loreto – Quevedo - Males Erazo, Estefanía (2024)
This research addresses a critical issue in flood control in the Loreto sector, focusing on the influence of the Baba Dam. This investigation proposes a comprehensive analysis of the situation, considering that the "Atascoso" stream passes through this sector, fed by several streams upstream connected to the Quevedo River. During heavy rains, the water level increases in the Loreto sector, causing flooding. This research focuses on evaluating the Baba Dam, which was built to regulate the flow downstream of the dam. The study also delves into the evaluation of anthropogenic effects caused by residents dumping garbage on the banks of the streams...........